2004
DOI: 10.1159/000082876
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Sensitization of the Hypothalamic-Pituitary Adrenal Axis Is Associated with Alterations of Hypothalamic and Pituitary Gene Expression

Abstract: We have previously reported that inescapable tail shock (IS) produces persistent changes in hypothalamic-pituitary-adrenal (HPA) axis function. These changes are manifest as an elevation in basal corticosterone (CORT) levels, a sensitization of adrenocorticotropin hormone (ACTH) and CORT responses to subsequent challenge, and a failure of dexamethasone to suppress both the ACTH and CORT responses to a subsequent challenge. The experiments presented here examine IS-induced alterations in the responsiveness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 106 publications
(66 reference statements)
3
25
0
Order By: Relevance
“…The long-lasting effect of a single exposure to stress on ACTH has also been reported in others studies (Johnson et al 2002a, Armario et al 2004, O'Connor et al 2004, and effects on basal Crh mRNA levels in the PVN and increased stressinduced Fos mRNA in the PVN have been described 24 h after exposure to an acute inescapable shock (O'Connor et al 2004).…”
Section: Discussionsupporting
confidence: 65%
“…The long-lasting effect of a single exposure to stress on ACTH has also been reported in others studies (Johnson et al 2002a, Armario et al 2004, O'Connor et al 2004, and effects on basal Crh mRNA levels in the PVN and increased stressinduced Fos mRNA in the PVN have been described 24 h after exposure to an acute inescapable shock (O'Connor et al 2004).…”
Section: Discussionsupporting
confidence: 65%
“…Whether this resistance to dexamethasone was the result of impaired effectiveness of negative feedback mechanisms or it was secondary to enhanced stimulatory inputs to the HPA axis is unclear at present. These authors have also described important changes in the HPA axis on the day after shock, which may contribute to the enhanced responsiveness (O'Connor et al, 2004): basal levels of mRNA for CRF in the PVN and for POMC in the anterior pituitary were elevated. In addition, when the animals were exposed to a novel environment they showed a greater induction of c-fos in the PVN and of c-fos and hnRNA for POMC in the anterior pituitary, strongly suggesting that exacerbated pituitary responsiveness to the novel environment was derived by the PVN.…”
Section: Response To Heterotypic Stressorsmentioning
confidence: 99%
“…In general, it is believed that pituitary ACTH responses to exogenous hypothalamic secretagogues, such as CRH and/or AVP, are of normal or slightly reduced amplitudes during chronic stress [6]. O’Connor et al[ 16] recently showed that inescapable tail shock produces persistent changes in the HPA axis function, including elevated basal CRH mRNA in the PVN and POMC mRNA in the AP with sensitization of the POMC hnRNA response to a subsequent challenge. Since the in vitro ACTH response to CRH challenge was blunted, they suggested that an increased hypothalamic drive was involved in the sensitization of the pituitary-adrenocortical axis.…”
Section: Introductionmentioning
confidence: 99%